Parental financial socialisation and financial knowledge: A structural equation modelling analysis - Adam Ndou (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2023)
Purpose: The main aim of the study was to investigate the impact of parental financial socialisation on financial knowledge of young black African adults in rural and low-income area in South Africa. This study was guided by family financial socialisation theory which is cognisant of the various family characteristics, such as family size and socioeconomic status, as predictors of financial outcome through their association with family socialisation process. Design/methodology/approach: The study used quantitative approach and survey design. Primary data on parental financial socialisation was collected from structured questionnaires. A survey was carried out on 500 young black African adults in Fetakgomo Tubatse and Intsika Yethu municipalities. The research hypotheses were tested using structural equation modelling (SEM) analysis. Findings: The study found that parental financial behaviour, parental financial discussion, parental financial communication, and parental financial teaching had significant positive impact on financial knowledge. It is observed that parental financial communication had the strongest impact on financial knowledge. Parental financial monitoring had a significant negative impact on financial knowledge. Thus, the overall results showed that parental financial socialisation has an impact on financial knowledge of young black African adults in rural and low-income area in South Africa. Research limitations/implications: Due to the low levels of general literacy among the respondents, which negatively affected data collection; some young adults did not understand the questionnaire and withdrew from participating in the study. Furthermore, even though confidentiality and anonymity were guaranteed, respondents were reluctant to participate in the study. They feared exposing their financial position and displayed a lack of trust. Originality/value: The current study contributed to the body of knowledge differently to the previous studies because it focused on parental financial socialisation of young black African adults in rural and low-income area. There is no study which has been conducted on parental financial socialisation impact on financial knowledge in rural and low-income area in South Africa. This makes this study so important and warrant that it should be carried out to provide the much-needed results that could help to improve the level of financial knowledge of young black African adults.
Keywords: D14; G51; G53; 330; Young black African adults; Parents; Financial knowledge; Parental financial socialisation